Increasing toughness by promoting discontinuous precipitation in Cu–Ni–Si alloys. (3rd May 2016) - Han, Seung Zeon; Lee, Jehyun; Goto, Masahiro; Lim, Sung Hwan; Ahn, Jee Hyuk; Kim, Sangshik; Kim, Kwangho
Abstract: The influence of precipitation morphology, including continuous precipitation (CP) and discontinuous precipitation (DP), on the mechanical behaviour of Cu–Ni–Si alloys was studied. The Cu–6Ni–1.5Si (in wt%) alloy was solution heat treated at 980 °C for 2 h and aged at 500 °C for 0.5 and 3 h to produce CP and DP structures. The DP specimen showed an abnormal increase in tensile ductility with increasing strain rate, unlike the CP counterpart. The impact toughness of the DP specimen was 1.6 times greater than that of CP specimen. The fracture mode in DP specimen was mostly dimpled rupture, while the mixed mode of cleavage fracture and dimpled rupture was noted on the CP specimen.